An interview with Biesterfeld Spezialchemie. Issue 2 (March 2019) - Garcia, Isabel
Abstract : Reinforced Plastics spoke with Dr. Johannes Martin from Biesterfeld Spezialchemie about composites manufacturing and current trends in the composite industry.